Making mergers and acquisitions work - Venzin, Markus; Vizzaccaro, Matteo; Rutschmann, Fabrizio (Emerald Publishing Limited, 2018)
For many industries, mergers and acquisitions have become the main pathway for reaching strategic objectives like growth, technological leadership, or efficiency in production and distribution. However, the success rate of most M&A deals is low - and flawed. Unrealistic synergies, wrong target selection, culture clashes and, most of all, weak post-merger integration processes pose huge challenges, and this book addresses the salient question of how to make M&A deals work. The authors offer readers unique access to each stage of the M&A process, with added depth and perspective provided by Prysmian - the global leader in energy and telecom cables. Prysmian's perspective enables the authors to deliver a manual for successful M&A in mature industries that require high levels of integration between operating companies. This collection of existing M&A experiences that identify clear action steps will be an essential tool for managers to develop their growth strategies and accelerate their post-merger integration processes. This guide will also prove useful for practitioners and academics as they seek to improve the ability of firms to conduct M&A, through dissemination in academic and executive classrooms.